Young Children with Type 1 Diabetes: Challenges, Research, and Future Directions - Streisand, Randi (2014)
The incidence of type 1 diabetes (T1D) in young children (age <6 years) is rising. Diabetes management guidelines offered by the American Diabetes Association and health care teams understandably place a high burden of responsibility on caregivers to check young children's blood glucose levels, administer insulin, and monitor diet and physical activity with the ultimate goal of maintaining tight glycemic control. Unfortunately, this tight control is needed during a vulnerable developmental period when behavior is unpredictable, T1D can be physiologically difficult to control, parenting stress can be elevated, and caregivers are strained by normal child caretaking routines. Despite the potentially different management needs, specific education and clinical services for managing diabetes in young children are rarely offered, and behavioral research with this young child age group has been limited in scope and quantity. Research findings pertinent to young children with T1D are reviewed, and potential clinical implications, as well as areas for future research, are discussed.